Lateral control strategy for a hypersonic cruise missile. (10th April 2017) - Fan, Yonghua; Yan, Pengpeng; Xu, Hongyang; Wang, Fan
Hypersonic cruise missile always adopts the configuration of waverider body with the restraint of scramjet. As a result, the lateral motion exhibits serious coupling, and the controller design of the lateral lateral system cannot be conducted separately for yaw channel and roll channel. A multiple input and multiple output optimal control method with integrators is presented to design the lateral combined control system for hypersonic cruise missile. A hypersonic cruise missile lateral model is linearized as a multiple input and multiple output plant, which is coupled by kinematics and fin deflection between yaw and roll. In lateral combined controller, the integrators are augmented, respectively, into the loop of roll angle and lateral overload to ensure that the commands are tracked with zero steady-state error. Through simulation, the proposed controller demonstrates good performance in tracking the command of roll angle and lateral overload.